Cannabinoid Receptor 1 Regulates Zebrafish Renal Multiciliated Cell Development via cAMP Signaling - Thanh Khoa Nguyen; Sophia Baker; Julienne Angtuaco; Liana Arceri; Samuel Kaczor; Bram Fitzsimonds; Matthew R. Hawkins; Rebecca A. Wingert (Journal of Developmental Biology)
Endocannabinoid signaling plays a significant role in neurogenesis and nervous system physiology, but its roles in the development of other tissues are just beginning to be appreciated. Previous reports have shown the presence of the key endocannabinoid receptor Cannabinoid receptor 1 (CB1 or Cnr1) in multiciliated (MCC) tissues and its upregulation in kidney diseases, yet the relationship between Cnr1 and renal MCC development is unknown. Here, we report that Cnr1 is essential for cilia development across tissues and regulates renal MCCs via cyclic AMP (cAMP) signaling during zebrafish embryogenesis. Using a combination of genetic and pharmacological studies, we found that the loss of function, agonism and antagonism of cnr1 all lead to reduced mature renal MCC populations. cnr1 deficiency also led to reduced cilia development across tissues, including the pronephros, ear, Kupffer’s vesicle (KV), and nasal placode. Interestingly, treatment with the cAMP activator Forskolin (FSK) restored renal MCC defects in agonist-treated embryos, suggesting that cnr1 mediates cAMP signaling in renal MCC development. Meanwhile, treatment with the cAMP inhibitor SQ-22536 alone or with cnr1 deficiency led to reduced MCC populations, suggesting that cnr1 also mediates renal MCC development independently of cAMP signaling. Our findings indicate that cnr1 has a critical role in controlling renal MCC development both via cAMP signaling and an independent pathway, further revealing implications for ciliopathies and renal diseases.